Successful Treatment for Hypercalcemia due to Cosecretion of Parathyroid Hormone-Related Protein and 1, 25-Dihydroxyvitamin D3 in Non-Small-Cell Lung Cancer: A Case Report and Literature Review. (3rd January 2020) - Ogawa, Takunori; Miyata, Jun; Fukunaga, Koichi; Kawana, Akihiko; Inoue, Takashi
Abstract : Hypercalcemia of malignancy frequently manifests as paraneoplastic syndrome in patients with solid tumors. A 71-year-old man was diagnosed with stage IIIB lung squamous cell carcinoma. Laboratory examination revealed high serum calcium concentration with elevated serum parathyroid hormone-related protein (PTHrP) and 1, 25-dihydroxyvitamin D3 levels. As the patient did not respond to the initial treatment with calcitonin, extracellular fluid infusion, and chemotherapy, systemic prednisolone was administered additionally. Thus, the levels of serum calcium normalized and PTHrP and 1, 25-dihydroxyvitamin D3 decreased simultaneously. To our knowledge, this is the first case report on the successful treatment of hypercalcemia of malignancy caused by PTHrP and 1, 25-dihydroxyvitamin D3 cosecretion in a patient with lung cancer.